2021
DOI: 10.7554/elife.57730
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial colonies in vitro elongate through collective effects

Abstract: Epithelial tissues of the developing embryos elongate by different mechanisms, such as neighbor exchange, cell elongation, and oriented cell division. Since autonomous tissue self-organization is influenced by external cues such as morphogen gradients or neighboring tissues, it is difficult to distinguish intrinsic from directed tissue behavior. The mesoscopic processes leading to the different mechanisms remain elusive. Here, we study the spontaneous elongation behavior of spreading circular epithelial coloni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 65 publications
1
36
0
1
Order By: Relevance
“…In line with earlier predictions from models of active liquid crystals [74], recent experiments on epithelial cells (MDCK) have shown that the self-propulsion of comet-like defects are correlated with the protrusion formation and elongation of initially circular cell colonies (Fig. 3d) [75]. Under cellular confinement, topological defects have been identified in cellular monolayers as pumps of cellular flows.…”
Section: Biological Functions Of Active Nematics In Tissuessupporting
confidence: 84%
“…In line with earlier predictions from models of active liquid crystals [74], recent experiments on epithelial cells (MDCK) have shown that the self-propulsion of comet-like defects are correlated with the protrusion formation and elongation of initially circular cell colonies (Fig. 3d) [75]. Under cellular confinement, topological defects have been identified in cellular monolayers as pumps of cellular flows.…”
Section: Biological Functions Of Active Nematics In Tissuessupporting
confidence: 84%
“…To identify the origins of the pulsatile collective flow, we ran numerical simulations of the tissue flow based on a vertex model [28]. In our model, cells were assigned a polarity vector that evolved over time according to a local alignment rule and a polarity diffusion.…”
Section: Numerical Simulations To Model Tissue Pulsatile Flowsmentioning
confidence: 99%
“…In this theoretical paper, we perform a systematic study of the role of bond tension fluctuations on the rheological properties of cellular networks. Our analysis is guided by a two-dimensional vertex model, which has been shown to provide a remarkable agreement with experimental data in the case of Drosophila wing morphogenesis [2] and for other confluent monolayers [6,[21][22][23]. To quantify the dynamical deformations of the cell network and relate them to cellular processes, we use a shear decomposition based on a triangulation of the cell network [24].…”
Section: Introductionmentioning
confidence: 95%